The Influence Of Academic Literacy On Students' Spirituality With The Campus Mosque Library As A Moderating Variable: A Quality Analysis And Case Study - Aid Samsudin; Momod Abdul Somad; Syihabuddin Syihabuddin; Edi Sursman (Jurnal Mamangan, 2023)
This study aims to analyze the influence of literacy on student spirituality moderated by the mosque library using a quality analysis approach and a quantitative moderation model. The novelty of this study lies in its attempt to integrate the dimensions of academic literacy, library quality, and spirituality into a single empirical framework that has not been widely explored before. This study also seeks to emphasize that the campus mosque library is not only a center of Islamic information, but also an instrument for forming an academic culture rooted in spiritual values. This study uses a quantitative approach with a moderated explanatory design. The main objective of this design is to examine the influence of literacy on student spirituality with the campus mosque library as a moderating variable. This approach was chosen because it is able to explain the causal relationship between variables empirically and assess the extent to which the strength of moderation influences the direction and intensity of the relationship. The results of the study indicate that student literacy has a positive and significant influence on spirituality where students with high levels of information, academic, and religious literacy show better spiritual awareness, both in the context of self-reflection and in academic and social behavior, then the quality of the campus mosque library directly influences the level of student spirituality. This shows that the mosque library functions not only as a literacy center, but also as a spiritual space that forms a balance between reason and heart, then student literacy directly influences the level of student spirituality and the campus mosque library acts as a positive moderating variable. In terms of quality, these results indicate that the dimensions of empathy and assurance are the main strengths of the mosque library, while responsiveness still needs to be improved, especially in digital services and operating hours. The conclusion is that student literacy and the campus mosque library influence student spirituality, and the campus mosque library is able to moderate the influence between student literacy on student spirituality in UI, Unpad, ITB, UIN and UPI Bandung Mosques and in terms of SEVQUAL quality in the good category.